Assessment of the accounting regulations in the Republic of Serbia: Application of cluster analysis - Sunčica Milutinović; Olivera Grljević; Dragomir Dimitrijević (Economic Themes, 2020)
The focus of the paper is on identification of hidden patterns in the opinion of accounting professionals, in order to identify the deficiencies in the legal accounting regulations and to examine their perspective on international and legal accounting regulations. The data collected through the questionnaire was divided using clustering data mining technique. We identified different groups of accountants with specific patterns regarding the expressed attitudes towards both regulations, as well as different groups of accountants with specific patterns regarding the way of obtaining information. The findings point to the prevailing negative attitude towards the legal accounting regulations quality, and differences in the habits and attitudes of certified and non-certified accountants, i.e. accountants who (don't) use International Financial Reporting Standards. Since there are four developed models, we used them as a basis for proposing a model of information seeking that could mitigate negative views on accounting regulations in the national economy. The key points of the proposed model are the introduction of compulsory continuous professional education and certification of all accountants, as well as activities for the popularization and accessibility of the international accounting regulations.
Keywords: M41; M48; C38; 330; International Financial Reporting Standards; accountingregulations; quality; accountants; clustering; data mining